2007
DOI: 10.1016/j.immuni.2007.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Ribosomal Protein L22 Selectively Impairs αβ T Cell Development by Activation of a p53-Dependent Checkpoint

Abstract: The alphabeta and gammadelta T lineages are thought to arise from a common precursor; however, the regulation of separation and development of these lineages is not fully understood. We report here that development of alphabeta and gammadelta precursors was differentially affected by elimination of ribosomal protein L22 (Rpl22), which is ubiquitously expressed but not essential for translation. Rpl22 deficiency selectively arrested development of alphabeta-lineage T cells at the beta-selection checkpoint by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
220
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(228 citation statements)
references
References 60 publications
(66 reference statements)
8
220
0
Order By: Relevance
“…It is now well documented that ribosomal stress, defined as an alteration of ribosome synthesis, can induce the activation of the tumor suppressor p53 blocking cell proliferation and activating apoptosis (Pestov et al, 2001;Sulic et al, 2005;Anderson et al, 2007;Panic et al, 2007;Danilova et al, 2008;McGowan et al, 2008;Fumagalli et al, 2009). Here, we report the analysis of the effect of RPS19 deficiency on the metabolism of two erythroid cell lines.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is now well documented that ribosomal stress, defined as an alteration of ribosome synthesis, can induce the activation of the tumor suppressor p53 blocking cell proliferation and activating apoptosis (Pestov et al, 2001;Sulic et al, 2005;Anderson et al, 2007;Panic et al, 2007;Danilova et al, 2008;McGowan et al, 2008;Fumagalli et al, 2009). Here, we report the analysis of the effect of RPS19 deficiency on the metabolism of two erythroid cell lines.…”
Section: Discussionmentioning
confidence: 92%
“…It involves four ribosomal RNA molecules, about 80 RPs and nearly 200 non-ribosomal factors that are required for the synthesis, maturation and export of the two ribosomal subunits (Fatica and Tollervey, 2002). A number of reports suggest that perturbations of ribosome biogenesis, owing to a variety of causes (ribosomal stress), can activate a specific checkpoint and block cell proliferation mostly through a p53-dependent mechanism (Pestov et al, 2001;Rubbi and Milner, 2003;Anderson et al, 2007;Panic et al, 2007;Danilova et al, 2008;McGowan et al, 2008;Fumagalli et al, 2009). This occurs, for example, in the case of conditional deletion of RPS6 (Volarevic et al, 2000;Sulic et al, 2005) or in response to drugs that disrupt nucleolar structures (Rubbi and Milner, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that overexpression of Bcl2 in Miz-1 ΔPOZ mice (Miz-1 ΔPOZ × Bcl2 Tg) rescues the apoptosis of Miz-1-deficient ETPs and partially rescues total thymic cellularity, but has no effect on the developmental block of Miz-1-deficient DN3 pre-T cells (21) a previous report that loss of Rpl22 correlates with an increased synthesis of p53 protein (29). Furthermore, this suggests that loss of Miz-1 leads to down-regulation of Rpl22, which increases the expression of p53 protein in DN3 pre-T cells.…”
Section: Cd19mentioning
confidence: 94%
“…However, although ablation of Rps6 in mouse liver was shown to activate p53 in an Rpl11-dependent manner, it did so in the absence of nucleolar disruption (Fumagalli et al, 2009), suggesting that inherent nucleolar breakdown may not be a necessary requirement for transmitting ribosome biogenesis stress signals to p53. The ablation of Rpl22, a RP that may be essential for new ribosome synthesis, but dispensable for translation, was found to selectively block ab T-cell, but not gd T-cell, lineage progression by inducing a p53-dependent arrest (Anderson et al, 2007). The selective block of development in one T-cell lineage, but not the other, provides evidence that p53-mediated surveillance of ribosome assembly may be more heavily weighted toward some cell types or possibly be stage specific.…”
Section: Rp Imbalances Activate P53mentioning
confidence: 99%